Mechanistic study of the induced decomposition of lophine-derived hydroperoxides and silylperoxides and synthesis of fluorescent arginine derivatives for labeling antimicrobial peptides - Boaro, Andreia (2021)
Fundação de Amparo a Pesquisa do Estado de São Paulo